Relationship between human leukocyte antigen (HLA)-DQA1*0102/HLA-DQB1*0602 polymorphism and preeclampsia - Mahmoud Mohammadi; Touraj Farazmandfar; Majid Shahbazi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Preeclampsia is a condition associated with systemic disorders in the mother and the fetus. However, the exact causes of preeclampsia are unknown, but several genetics and environmental factors play role in development of this disease. Major histocompatibility complex role is very important during pregnancy through which the fetus is not rejected by mother’s immune system. Objective: In this study, we investigated the relationship of the human leukocyte antigen (HLA)-DQA1*0102/HLA-DQB1*0602 polymorphism with preeclampsia. Materials and Methods: Genomic DNA of 181 pregnant women with a history of preeclampsia as the case group and 228 pregnant women with no history of preeclampsia as the controls were extracted. The HLA-DQA1*0102/HLA-DQB1*0602 polymorphisms of all DNA samples were identified by the SSP-PCR method. Frequencies difference of variables between case and control groups were calculated by Chi-square test. The ethnic origin of the participants in this study was extracted from their medical records. Results: There was a significant association between preeclampsia and Sistani ethnic group (p=0.031). Moreover, there was a significant association between preeclampsia and frequencies of allele HLA-DQB1*0602 (p<0.001), and genotypes of heterozygote (+0102/-0602) (p<0.001) and negative homozygote (-0102/-0602) (p=0.005). There also was an association between allele HLA-DQB1*0602 and preeclampsia in Fars ethnic group (p=0.028). Conclusion: It seems that immune incompatibility may have an important role in preeclampsia predisposition. According to our results, the lack of locus HLA-DQB1*0602 may be a risk factor for preeclampsia.